Implementasi Penggunaan Aplikasi Visual Classroom dalam Meningkatkan Partisipasi Siswa dalam Pembelajaran Jarak Jauh di SMK Auto Matsuda - Herdian, Iqbal; Haerudin, Dodi Ahmad (Indo-MathEdu Intellectuals Journal, 2025)
Distance learning during the COVID-19 pandemic presents major challenges, one of which is low student engagement in the online learning process. The Visual Classroom application is offered as a solution by providing interactive features and attractive visual media to increase student participation. This study aims to analyze the effect of using the Visual Classroom application on student participation in distance learning at SMK Auto Matsuda. The research method used is quantitative with a descriptive design and simple linear regression analysis. The research sample consists of 23 students who actively use the application. Data was collected through questionnaires that had been tested for validity and reliability. The results showed that the use of Visual Classroom had a significant effect on increasing student participation, with an F test value of 6.004 (p < 0.05) and a t value of 2.450 (p < 0.05). Student responses were also positive, with an average score of 72.43 in the good category. These findings confirm that Visual Classroom is effective in increasing student engagement in distance learning. This study recommends optimizing the interactive features of the application and improving teacher competence to maximize its use.